1123 An Audit of Pick-Up Rate of Random Colonic Biopsies. (12th October 2021) - Zulfiqar, S; Baig, H; Buksh, M
Abstract: Aim: We aimed to evaluate optimal random biopsy criteria are being followed in our institution to increase the diagnostic yield of a subsequent histopathological examination and to reduce the number of unnecessary biopsies in which histopathology is unlikely to deliver clinically useful information and causing a burden on health resources in terms of cost and manpower. Method: Our study was a retrospective on 419 random colonoscopy biopsies performed over 6 months. Data collection included variables such as age, gender, indications, request of urgency, and histology findings. Data analysis was done descriptively. Results: Out of 419 random biopsies, only 10.02% had positive findings. The total number of histology results with microscopic colitis was 10. The main indication of the random colonic biopsy was a change in bowel habits (328 cases) followed by significant diarrhea greater than 50 years in 20 cases. In patients with a change in bowel habits, 2.44% of histopathology specimens revealed microscopic colitis. The percentage of random colonic biopsy histology in patients greater than 50 years with significant diarrhea showed microscopic colitis was 10%. Conclusions: Our study revealed random biopsy during colonoscopy should only be done in selected patients otherwise it has low diagnostic yields biopsy and should only be reserved for patients with risk factors for optimum utilization of health resources and to reduce the cost burden. A scoring system may be helpful to risk-stratify patients in low and high risk for MC to determine which patients qualify for RCB.